Geração de mapas temáticos para recomendação de fertilizantes utilizando a plataforma AgDataBox - Silva, Franciléia de Oliveira e (2022)
The nutrients recommendation maps are used to apply fertilizers at a variable rate. This is one of the most applied precision agriculture techniques to maximize the productivity of our main crops, soybeans and corn, in Brazil. Thus, this research aimed at generating NPK recommendation maps, based on the sampling of these nutrients on soil, in order to provide accurate information to be applied in soybean and corn, at a variable rate and by management zones, using the AgDataBox platform. Besides, it also compares the cost of applying urea, simple superphosphate and potassium chloride fertilizers in conventional and precision agriculture. The research was carried out with data obtained in two experimental areas, in the Western Paraná region, Brazil. Soil sampling was carried out according to the recommendations of the quality assurance manual of the Agricultural Mechanization and Precision Agriculture Laboratory. The entire nutrient recommendation process was carried out by using the AgDataBox platform. Thus, the doses for nitrogen fertilization in corn were obtained by the recommendation method, EPMO, which considers the expectation of productivity and organic matter content in soil. The doses to apply simple superphosphate and potassium chloride in corn and soybean were obtained by the D methods, which considers only the content of each nutrient on soil, and by the EP method, which considers the nutrient content on soil and the expected productivity. Thematic maps and management zones were generated based on specific protocols on this issue. NPK nutrients showed spatial and temporal variability in the studied areas. The recommendation maps have recorded some variability of nutrients in those areas and provided adequate doses to be applied at a variable rate. Zones considered homogeneous were identified in both studied areas, which presented the best separation with two classes. The application of fertilizers at the management zones has assured to be more economical than at the conventional agriculture ones. The AgDataBox platform has shown to be efficient in generating thematic maps of recommendations for urea, simple superphosphate and potassium chloride fertilizers to be applied in soybean and corn crops at a variable rate, and in defining management zones.